Pengaruh Profitabilitas, Leverage, Firm Size, dan Growth Opportunity Terhadap Cash Holding Perusahaan (Studi Kasus Perusahaan Manufaktur yang Terdaftar Pada Bursa Efek Indonesia Periode Tahun 2013-2017) - Saputri, Erdian; Kuswardono, Anon (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This study aims to analyze the effect of Profitability, Leverage, Firm Size, and Growth Opportunity on Cash Holding in manufacturing companies listed on the Indonesia Stock Exchange. The research observation period is 2013-2017. The number of samples in this study were 20 samples from 154 selected companies based on the purposive sampling selection technique and using secondary data types. The analysis used is panel data regression with a fixed effect model. The results of this study state that profitability, leverage, firm size, and growth opportunity are proven simultaneously affect the cash holding rate. From the results of the partial test, profitability and firm size have a positive and significant influence on the level of the company's cash holding. While leverage has a negative and significant influence on the level of cash holding and growth opportunity has no significant effect on cash holding rates.